Genetic associations as indices for assessing nitrogen transformation processes in co-composting of cattle manure and rice straw. (November 2019) - Sun, Yu; Sheng, Siyuan; Jiang, Xin; Bello, Ayodeji; Wu, Xiaotong; Meng, Qingxin; Deng, Liting; Xu, Xiuhong; Li, Hongtao
Graphical abstract: Highlights: N transformation processes were coupled on molecular level (functional genes). Functional gene groups could be used to quantify N transformation. AmoA/(napA + narG) mediated both NO3 − -N and NO2 − -N transformation. AmoA/anammox (−0.7172) and (nirK + nirS)/nosZ (−0.6626) determined TN removal. SNAD processes coexisted in nitrogen transformation in composting. Abstract: In this study, mechanism of nitrogen transformation was investigated in terms of genetic associations (nitrogen-related gene groups) in co-composting of cattle manure and rice straw. Mutual validation among KEGG, Pearson correlation, stepwise regression, and Path analyses indicated that the functional genes synergistically affected on nitrogen transformation in composting process. NxrA/qnorB (0.9419 ± 0.0334) and (amoA + anammox)/Bacteria (0.7187 ± 0.0334) were the key functional gene groups mediating NH4 + -N transformation. AmoA/(narG + napA) (−0.8400 ± 0.0129), amoA/bacteria (0.8692 ± 0.0273), and (nirK + nirS)/nosZ (1.1652 ± 0.0089) determined NO3 − -N, NO2 − -N and N2 O transformation, respectively. AmoA/(napA + narG) mediated both NO3 − -N and NO2 − -N transformation. AmoA/anammox (−0.7172 ± 0.0591) and (nirK + nirS)/nosZ (−0.6626 ± 0.0825) served as predominant factors for total nitrogen removal. These results provided a molecular-level insight that nitrification, anaerobic ammonia oxidation and denitrification (SNAD) might simultaneously contribute to nitrogen transformation during composting, rather than sequentially.